Implementasi E-Modul Interaktif dalam Meningkatkan Motivasi dan Hasil Belajar Siswa pada Pembelajaran Biologi di SMA Negeri 1 Gondang - Ninik Hartati (Jurnal Pendidikan Madrasah, 2022)
This study aims to determine the influence of the application of interactive e-modules on motivation and learning outcomes simultaneously and conventional e-modules (as a control group). This type of research is quasi-experimental and designed with a non-equivalent pre and post test control group design. The population in this study was the entire class X at SMA Negeri 1 Gondang. Samples were selected by a simple random sampling technique, class X MIPA 2 as the control class, and class X MIPA 3 as the experimental class. Learning motivation data is obtained through filling out a likert-scale learning motivation questionnaire, while learning outcomes data is obtained through learning outcomes evaluation tests. The data were analyzed descriptively and hypothesis testing using the Manova Test. The results showed that (1) There was a significant difference between motivation and learning outcomes simultaneously (p < 0.05), (2) There was no significant difference in student learning motivation, the type of module only affected 2.90% of student learning motivation (p > 0.05) and (3) There was a significant difference in learning outcomes between students who were taught by applying interactive e-modules and conventional e-modules, the type of module affected by 30.80% on student learning outcomes (p < 0.05). The application of interactive e-modules affects student motivation and learning outcomes simultaneously, but does not affect student learning motivation.